The Financial Inclusion Gender Gap: A Case Study of Households in Indonesia - Meigendaris Surtiabadi Putri; Djoni Hartono (Universitas Negeri Malang, 2024)
The financial inclusion gender gap is one important issue that has become a global concern because financial inclusion can enhance women's empowerment in many aspects. Using the Fairlie Decomposition method, this study aims to describe whether there is financial inclusion gender gap in Indonesia and analyze what factors contribute significantly to the gap. It is one of the earliest analyses of the household financial inclusion gender gap and its underlying causes in Indonesia using the decomposition method, which is considered the most suitable for quantifying each factor's contribution to the gap. The findings reveal that female-headed households have less access to financial inclusion. The biggest contributions of this gap are explained by differences in socioeconomic characteristics among genders, such as the limitations of the female-headed household in owning a mobile phone, the lower participation in the formal labor market, and the lower level of education. Thus, policies that only focus on removing financial inclusion barriers from the supply side are not effective enough because differences in characteristics among genders or from the demand side have become the prominent cause of the financial inclusion gender gap.